Is the Parkland formula still the best method for determining the fluid resuscitation volume in adults for the first 24 hours after injury? — A retrospective analysis of burn patients in Germany. Issue 4 (June 2021) - Daniels, Marc; Fuchs, Paul Christian; Lefering, Rolf; Grigutsch, Daniel; Seyhan, Harun; Limper, Ulrich; the German Burn Registry,; Schiefer, Jennifer Lynn
Highlights: Parkland formula is an effective method for calculating fluid resuscitation volume. Parkland formula is not inferior to modern goal-directed therapy methods. First-week survival of burns patients is increased on using the Parkland formula. Abstract: Background: R Rapid fluid resuscitation is a crucial therapy during the treatment of patients with extensive burns. In 1968, the Parkland Formula was introduced for the calculation of the estimated volume of the resuscitation fluid. Since then, different methods for the calculation of fluid resuscitation volume have been developed. We aimed to evaluate if the Parkland formula is still the most effective method for fluid resuscitation volume calculation in burn patients. Methods: In the period between January 2015 and January 2019, data from 569 patients over 16 years old with burns of more than 20% total body surface area (TBSA) and at least 15% TBSA full thickness burns were entered in the German burn registry. The patients were divided into 5 groups (0, +1, −1, +2, −2) according to the volume of the resuscitation fluid they received. Group 0 patients received the amount of fluid calculated according to the Parkland formula (n = 83). The 4 other groups received reduced (-1, -2) or increased (+1, +2) fluid volumes in comparison to the value obtained by the Parkland formula. Results: Patients in Group 0 presented a significantly lower mortality in the first week (4.5%) compared to groups –2 (16.7%) and group +2 (19.5%) (p = 0.021). Furthermore, the mean number of operations in group +2 (5.81) was higher than in group −2 (3.81). Surviving patients from group +2 presented a longer hospital stay (68.1 days) compared to the other groups. Additionally, the logistic regression analysis showed a higher survival of patients in groups −2 and −1 (regression coefficients −0.11 and −0.086; Odds Ratio 0.896 and 0.918; 95% Confidence Interval (CI) 0, 411–1.951 and 0.42–2.004). Conclusion: In this retrospective study, register based analysis a restrictive fluid regime was associated with a higher survival compared to the liberal Parkland guided fluid regime.